Evaluation of Flavonoid Content from Shoot Culture of Gynura procumbens in Balloon-type Bubble Bioreactors - Ira Nailas Sa'adah; Yosephine Sri Wulan Manuhara; Alfinda Novi Kristanti (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
Gynura procumbens has been widely used to treat several health disorders, such as hyperglycemia, hypertension, diabetes, and allergies. This study aimed to determine the flavonoid content of G. procumbens cultured in a balloon-type bubble bioreactor using various sucrose concentrations (10, 30, and 50 g/L) and explant densities (5, 10, and 15 explants). The plant parts used were stem nodes of G. procumbens, grown in a balloon-type bubble bioreactor using Murashige and Skoog (MS) liquid media with IAA 2 mg/L and BAP 4 mg/L. The total flavonoid content was measured using a UV-Vis spectrophotometer (λ= 510 nm), and the flavonoid profile was tested using thin-layer chromatography (TLC). The administration of 10 g/L sucrose produced the highest total flavonoid production. In the treatment of explant density, the most increasing total flavonoid production was obtained in the treatment of 5 explants. The TLC results showed that each treatment forms spots like standard. This study proved that sucrose and explant densities culture on balloon-type bubble bioreactor method had optimized the production of flavonoids of plant shoots of G. procumbens culture.